1979
DOI: 10.1007/bf02024108
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of alterations in the histamine-diamine oxidase system during acute intestinal ischaemia in pigs, dogs and rabbits: Evidence for a uniform pathophysiological mechanism?

Abstract: Among various vasoactive substances histamine was also suggested to induce circulatory arrest following superior mesenteric artery occlusion. Thus the involvement of the histamine-diamine oxidase system was studied in intestinal ischaemia using three animal species. In pigs, dogs and rabbits aminoguanidine, the specific inhibitor of diamine oxidase, shortened the survival time after mesenteric infarction. Under these conditions the diamine oxidase activity in the intestinal wall was reduced in animals treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1980
1980
2006
2006

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…DAO functions as a regulator in rapidly proliferating tissue by deaminating these polyamines [4]. On the other hand, DAO has been reported to protect the organism against the deleterious effects of at least one vasoactive amine, histamine, after intestinal ischemia-reperfusion [22]. Elevated SSAO activity, which is observed in diabetic states, has been associated with reduced elasticity of arteries [23]; congeners of DAO may have yet other actions.…”
Section: Discussionmentioning
confidence: 98%
“…DAO functions as a regulator in rapidly proliferating tissue by deaminating these polyamines [4]. On the other hand, DAO has been reported to protect the organism against the deleterious effects of at least one vasoactive amine, histamine, after intestinal ischemia-reperfusion [22]. Elevated SSAO activity, which is observed in diabetic states, has been associated with reduced elasticity of arteries [23]; congeners of DAO may have yet other actions.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, using a paradigm that provoked a massive release of endogenous HA, we confirmed the observations of others [21] who showed that AG augmented the levels of HA given to dogs. In dogs and other species, AG shortened survival times following induction of intestinal ischemia [22,23], presumably by extending the duration of histamine's deleterious effects.…”
Section: Discussionmentioning
confidence: 99%
“…At least it was found by KUSCHE et al [7,8] that aminoguanidine following mesenteric infraction increased the plasma histamine levels and aggravated severely the development of shock in rabbits, dogs and pigs. This effect could be reversed by histamine receptor antagonists.…”
Section: Introductionmentioning
confidence: 94%